Effect of Tachinid Parasitoid Exorista japonica on the Larval Development and Pupation of the Host Silkworm Bombyx mori - Dai, Min-Li; Ye, Wen-Tao; Jiang, Xue-Jian; Feng, Piao; Zhu, Qing-Yu; Sun, Hai-Na; Li, Fan-Chi; Wei, Jing; Li, Bing (Frontiers in Physiology, 2022)
The Tachinidae are natural enemies of many lepidopteran and coleopteran pests of crops, forests and fruits. However, host-tachinid parasitoid interactions have been largely unexplored. In this study, we investigated the effects of tachinids on host biological traits, using Exorista japonica, a generalist parasitoid, and the silkworm Bombyx mori, its lepidopteran host, as models. We observed that E. japonica parasitoidism did not affect silkworm larval body weight gain and cocooning rate, whereas caused shortened duration of molting from the final instar to the pupal stage, abnormal molting from larval to pupal stages and a subsequent decrease in host emergence rate. Moreover, a decrease in juvenile hormone (JH) titer and an increase in 20-hydroxyecdysone (20E) titer in the hemolymph of parasitized silkworms occurred. The transcription of JH and 20E responsive genes was downregulated in mature parasitized hosts but upregulated in parasitized prepupae while Fushi-tarazu factor 1 (Ftz-f1), a nuclear receptor essential in larval ecdysis, showed dramatically reduced expression in parasitized hosts at both mature and prepupal stages. Moreover, the transcriptional levels of BmFtz-f1 and its downstream target genes encoding cuticle proteins were down regulated in epidermis of parasitized hosts. Meanwhile, the content of trehalose was decreased in the hemolymph while chitin content in the epidermis was increased in parasitized silkworm prepupae. These data reveal that the host may fine-tune JH and 20E synthesis to shorten developmental duration to combat established E. japonica infestation while E. japonica silences BmFtz-f1 transcription to inhibit host pupation. This discovery highlights the novel target mechanism of tachinid parasitoids and provides new clues to host/tachinid parasitoid relationships.